Algorithmic governmentality and subjectivity - Barboza, Romina Andrea (2022)
Zapping, multitasking and constant scrolling place us in a state of “distraction” and normalized attention, challenges that imply thinking about the digital infrastructure of culture and algorithmic governmentality in broader terms: thinking about the dominant affective regime (by which distraction, indignation and social division are maintained). To do this, I delve into the relationship between the neoliberal rationality of the culture of connectivity and affective self-precarization. In this crossroads, digital devices fulfill an important function, not so much because of the content but because they modulate certain modes of attention, temporality and self-representation and self-control. The overlap between platform capitalism and the current affective regime places the need to rethink self-care today in relation to digital media. I aim to analyze the contemporary way of stulticia and rethink the practices of the self through the re-elaboration of classic subjectivation exercises (from the Hellenistic-Roman Era). In other words, to rethink the need for a paraskeue, that is, an equipment of true discourses in which the subject assumes both its knowledge value and its action value. Exercises (listening and literacy) are proposed that aim to provoke a subversion of power with a view to transforming the dominant modes of subjectivation or self-subjectivation.